How do psychedelics impact people with a history of non-affective psychosis? A qualitative study - Dourron, Haley Maria; Copes, Heith; Grossman, Daniel H.; Bradley, Melissa; Nicholas, Christopher R.; Turner, Jessica A.; Allen-Clark, Gaige; Gossage, Maggie; Hendricks, Peter S. (Frontiers in Psychiatry, 2025)
BackgroundPeople with a history of psychotic disorders are excluded from contemporary trials of psychedelic-assisted therapy. Although survey studies have explored the impact of naturalistic psychedelic use on people with a history of psychotic disorders, a qualitative study has yet to examine the subjective effects of psychedelic use in this population during both the acute effects and perceived long-term impacts.MethodTwo semi-structured in-depth interviews were conducted with participants (n = 19) who had used psychedelics after the diagnosis of non-affective psychotic disorders (NAPD). Interviews probed the perceived positive and negative effects of psychedelic use. Data were analyzed using reflexive thematic analysis.ResultsWe constructed three major themes: 1) common challenges during the acute effects of psychedelics; 2) psychosis-specific psychedelic experiences; and 3) post-acute and long-term effects. In the common challenges of psychedelic use theme, participants often described experiences with transient anxiety, which sometimes resulted in brief self-reported hospitalizations. In the psychosis-specific psychedelic experiences theme, the subthemes consisted of psychedelics during and after psychosis, self-compassion and reduced self-stigma, and insight into hallucinations and delusions. The post-acute and long-term effects theme included subthemes of positive effects, negative effects, and a lack of long-term effects. Overall, most participants described some benefits of psychedelics, but the durability of perceived benefits varied widely.ConclusionPsychedelics might have heterogeneous impacts on people with NAPD, including both risks for harm and potential benefits. Our findings may assist in the development of safety and tolerability trials, highlighting the need for more nuanced work that examines how psychedelics impact people with NAPD.